DEVELOPMENT OF ROBLOX-BASED LEARNING MEDIA (ROBOKASDIS) TO IMPROVE FIRST-GRADE ELEMENTARY STUDENTS’ UNDERSTANDING - Sherly Marthalia; Nita Nurizki; Moh Hafidhull Ullum; Ani Nur Aeni (Atta'dib Jurnal Pendidikan Agama Islam, 2026)
This study developed and evaluated RoboKasDis, a Roblox-based educational game for elementary Islamic Religious Education, designed to improve students' understanding of Islamic religious values and character traits (gratitude and discipline). Using the ADDIE Research and Development model, the study involved 19 first-grade students at SDN Cikurubuk. The results showed significant effectiveness: average test scores improved from 78.53 (pre-test) to 100 (post-test), with high quiz scores averaging 93.68. Observations also highlighted increased student enthusiasm and active participation. In conclusion, RoboKasDis is an effective interactive tool for boosting learning outcomes, motivation, and character development.